Revitalizing Orin Farm Settlement for Food Security in Ido Region, Nigeria. - Joseph Omoniyi , Basorun; Olusola, Daramola Joshua (Advances in Social Sciences Research Journal, 2019)
Ido region in Ekiti State, Nigeria experiences economic shortage specific to food production. This associates with difficulty in food distribution on account of poverty, population growth and inadequate social infrastructure. Personal observation and verbal interview with the residents of the area revealed high level of food insecurity. Majority of the young school leavers and uneducated working class have moved to urban areas due to lack of social infrastructure and fund which represent the economic power to embark on commercial farming. This paper emphasizes the need for Ekiti State Government to propel commercial agriculture by reviving Orin farm settlement for sustainable food production. No doubt, broad based policies are required to diversify the economy of the region through a well-focused food security agenda.